2020
DOI: 10.21203/rs.3.rs-47891/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Prognostic Value of Modified Glasgow Prognostic Score in Pancreatic Cancer: A Meta-analysis

Abstract: Background: Several studies were conducted to explore the prognostic value of modified Glasgow Prognostic Score (mGPS) in pancreatic cancer, which reported contradictory results. The purpose of this meta-analysis was to summarize the prognostic value of mGPS in pancreatic cancer by investigating the correlation between mGPS and overall survival (OS). Methods: A systematic literature search was performed in PubMed, EMBASE, ISI Web of Science, Cochrane library databases and OVID to identify eligible studies publ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 44 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…Only 3 studies explored the predictive role of pretreatment mGPS for PFS in SCLC patients. [31,34,35] The pooled results demonstrated that pretreatment mGPS was significantly associated with PFS (HR = 1.40, 95% CI: 1.13–1.74, P = .002; I 2 = 0.0%, P = .405) (Fig. 3) and patients with elevated mGPS experienced worse PFS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only 3 studies explored the predictive role of pretreatment mGPS for PFS in SCLC patients. [31,34,35] The pooled results demonstrated that pretreatment mGPS was significantly associated with PFS (HR = 1.40, 95% CI: 1.13–1.74, P = .002; I 2 = 0.0%, P = .405) (Fig. 3) and patients with elevated mGPS experienced worse PFS.…”
Section: Resultsmentioning
confidence: 99%
“…Tan et al included 13 studies involving 12,524 urothelial carcinoma patients and demonstrated that a high mGPS was obviously associated with poor OS (mGPS 0/1: HR = 1.33, P = .001; mGPS 0/2: HR = 2.02, P < .001) and PFS (mGPS 0/1: HR = 1.26, P = .021; mGPS 0/2: HR = 1.76, P = .013), recurrence-free survival (RFS) (mGPS 0/1: HR = 1.36, P < .001; mGPS 0/2: HR = 1.70, P < .001) and cancer-specific survival (mGPS 0/2: HR = 1.81, P < .001). [21] Besides, Wu et al [29,33,34,36,37] 1.81 0.96-3.41 .065 92.1 <.001 Japan 4 [30][31][32]35] 2.15 1.68-2.75 <.001 0.0 .953 Tumor stage Mixed 7 [29,30,33,34,[36][37][38] 1.77 1.20-2.63 .004 89.5 <.001 Extensive 3 [31,32,35] 2.37 1.57-3.58 <.001 0.0 .993 Treatment Mixed 3 [29,30,32] 2.66 1.59-4.46 <.001 57.4 .096 Chemotherapy 6 [31,[33][34][35][36][37] 1.68 1.00-2.82 .052 88.7 <.001 Comparison of mGPS mGPS 0 vs 1 5 [29,30,32,33,38] 1.31 1.16-1.49 <.001 0.0 .902 mGPS 0 vs 2 5 [29,30,32,33,38] 2.75 1.77-4.28 <.001 81.3 <.001 Progression-free survival 3 [31,34,35] 1.40 1.13-1.74 .002 ...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immune-nutritional indexes, including PNI, 12 mGPS, 13 NLR, 14 PLR, 15 RDW, 16 and CONUT, 17 were determined based on previous reports. PNI, NLR, and PLR were composed of continuous data, whereas CONUT and mGPS were composed of noncontinuous data.…”
Section: Calculation Of Various Immune-nutrition Scoresmentioning
confidence: 99%
“…8,9 In addition, systemic inflammatory responses are significantly associated with a progressive decline in nutrition and function as well as subsequent adverse outcomes in patients with cancer. 10,11 Various immune-nutritional assessment methods exist, including the prognostic nutrient index (PNI), 12 modified Glasgow prognosis score (mGPS), 13 neutrophil lymphocyte ratio (NLR), 14 platelet-tolymphocyte ratio (PLR), 15 red blood cell distribution (RDW), 16 and controlling nutritional status (CONUT), 17 which have all been reported to predict the prognosis of pancreatic cancer. However, it remains unclear which immune-nutritional index is the most accurate for evaluating the prognosis of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%